Legal Protection of Children Born From Contract Marriage - Lubis, Eliya Nova; Arifin, Muhammad; Erwinsyahbana, T. (Budapest International Research and Critics University, 2021)
Contract marriage is a marriage that is not religiously valid and not recognized under the laws of the State. The phenomenon of contract marriage still often occurs in some areas in Indonesia. Although in contract marriage is not desirable for children, but often occurs children born from the marriage of the contract. Contracted marriage children are not recognized for the validity of their legal status both in the perspective of Islamic jurispruding and in the Marriage Law and also the Compilation of Islamic Law. This research is descriptive of analysis and uses legal research, with a research approach to legal principles. The source of this research data is in the form of secondary data. The procedure of retrieving and collecting data is carried out by means of library research. Data analysis in this study is done through qualitative data analysis. The result of the study is that the legal status of contract marriage in the perspective of Islamic fiqh is invalid, as it has been prohibited by the provisions of the syara'. Contract marital status under Law No. 1 of 1974 is not recognized because it is not in accordance with the principles of marriage law, e.g. marriage in contract marriage is only intended for a while, and contract marriage is not recorded in the state institution authorized for it. That the position of a child born from a contract marriage in the perspective of Islamic fiqh includes a child of adultery, since contract marriage which in the classical fiqh perspective is known as mut'ah marriage has been abolished by the syara's provisions. According to Law No. 1 of 1974, the position of children born from contract marriage is an illegitimate child, because it was born as a result of an unauthorized marriage.